The tax game: Determinants of tax aggressiveness in Indonesian manufacturing giants - Prathama, Rafi; Betan, Henriantony Hipa; Mardhianindro, Berry; Khalil E, Muhammad; Diandria, Davinnizam Ramadhan; Wijaya, Suparna (WIM Solusi Prima, 2025)
This research examines the factors that influence tax aggressiveness in manufacturing companies in Indonesia listed on the Indonesia Stock Exchange (BEI) during the 2022-2023 period. Tax aggressiveness is the actions taken by companies to minimize their tax liabilities through legal and illegal means. The factors analyzed in this research include company characteristics such as profitability, leverage, company size, capital intensity, inventory intensity, and liquidity, as well as corporate governance mechanisms such as controlling share ownership and the proportion of independent commissioners. The findings of this research contribute to the development of theory and knowledge in the fields of accounting and taxation and provide insight for investors in making investment decisions.